Konseling Behavioral Terhadap Remaja Yang Kecanduan Alkohol Akibat Broken Home - Muhammad Fathur Rohman; Ati Kusmawati; Gadis Zabina Ahya’ul Sena; Muhammad Sofwan Apriliansyah (Concept: Journal of Social Humanities and Education, 2024)
The research is aimed at knowing the problems of the client and the causes of the client's social irregularities. The study uses qualitative research methods. Data collection techniques are performed with observation, interviews and literature studies. The result of this study is the factor behind the social irregularities of adolescents who experience or live in broken home circles. Most youths commit this social aberrant because they want to shift their weight, their unhinged teenage behavior is also one of the factors that causes youths to commit deviations or delinquency, making them more susceptible to the adverse effects of their surroundings. A typical example of broken home adolescents involves alcoholics, drug use, and so forth. At present, however, social deviations are not limited to the person or youth of broken home, illness. Delinquency seems to be common in teens or in juvenile delinquency often results in achievement (pride) in order to make it a good, fun, fun youth. This factor is due to the rapid growth of globalization and modernization that many outside cultures are introduced into Indonesia and are affecting social aberrant behavior in the youth.